Gastos ambientais do governo federal: Aperfeiçoamentos metodológicos, atualizaç\~ao para o período Bolsonaro e avaliaç\~ao da atuaç\~ao governamental, em especial no combate ao desmatamento na Amazônia. A passagem da boiada - Jo\~ao Paulo Viana (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– This study analyzes the federal government's environmental expenditures between 2001 and 2022 by applying the United Nations (UN) Classification of Environmental Activities (CEA) to budgetary actions. In addition, a qualitative and comparative analysis is carried out of expenditures and results achieved in controlling deforestation and burning in the Amazon between the Bolsonaro period and previous governments, in the face of deleterious changes introduced in environmental policies during his administration. The federal government spent an average of BRL 7.99 billion/year on the environment between 2001 and 2022, which corresponds to a total of BRL 175.75 billion over 22 years. Environmental spending represented, on average, 0.11% of gross domestic product (GDP)/year and 0.26% of total federal government spending/year. In absolute values, total government spending in the four-year period corresponding to the Bolsonaro administration was BRL 33.28 billion, slightly lower than spending in the immediately previous four-year period, the Dilma/Temer administration (BRL 33.31 billion). That is, from a global point of view, environmental spending was stable in the Bolsonaro government. As in the previous research, the highest expenses occurred in three themes: the management of aquatic resources (BRL 50.17 billion), especially with the payment of closed season insurance for artisanal fishermen, in other environmental protection activities (BRL 44.58 billion), which includes the management and administrative costs of the Ministry of the Environment and related institutions, and the management of liquid effluents and wastewater (BRL 39.23 billion). If, from a global perspective, the trend of environmental spending was one of stability, the behavior by the thematic approach adopted in the research reveals a different, more complex and worrying picture. Two classes, in particular, draw attention due to the magnitude and implications of the reduction in expenses, that corresponding to sanitation, which lost about BRL 2.2 billion in the 2019-2022 quadrennium compared to the 2015-2018 quadrennium, and the class that contains the salaries of civil servants, with a reduction of approximately BRL 1.0 billion, which indicates personnel loss. Changes in budgetary governance that occurred during the Bolsonaro government, with a greater role for the Legislative Branch, may explain the low amounts spent on seven of the fifteen classes of environmental themes studied. Such amounts, less than BRL 20 million a year, hardly make the implementation of environmental public policies on a national scale possible. In the case of more expressive increases in expenses, the environmental benefits must be viewed with reservations, as in the case of fighting deforestation and forest fires, which, despite greater budgetary support, including the great involvement of the Armed Forces, failed to adequately control these phenomena. The reversal of the trend of continuous increase in the deforestation rate measured by the National Institute for Space Research (Instituto Nacional de Pesquisas Espaciais - Inpe) in the last year of the Bolsonaro administration may reflect the change in governance of the structure to fight deforestation that began in 2021, with the demobilization of the Armed Forces from this task, which became coordinated by the Ministry of Justice and Public Security (Ministério de Justiça e Segurança Pública - MJSP). The inverse correlation between spending and the deforestation rate found in the research indicates that budget support is essential for controlling phenomena such as forest fires and deforestation, but the existence of a well-structured public policy and institutional articulation are essential requirements for the success of government intervention.
Keywords: Q00; 330; Brazil; federal government; environmental expenditures; environmental statistics; public budget; deforestation; Classification of Environmental Activities; Bolsonaro government; Armed Forces